Rancang Bangun Alat Pengiris Singkong dengan Metode Quality Function Deployment (QFD): [Design and Development of a Cassava Slicing Tool using The Quality Function Deployment (QFD) Method] - Christiani, Agustina; Theresia, Jessica (FaST : Jurnal Sains dan Teknologi, 2025)
This research was conducted to design and develop a cassava slicing tool for the UMKM (Micro, Small, and Medium Enterprises) "Keripik Singkong Bu Supiah" located in Keranggan Village. The design and development process of this slicing tool was carried out using the Quality Function Deployment (QFD) approach and a House of Quality (HOQ) matrix, which was employed to gather user needs (voice of the customer) and then further analyzed to generate HOWs (engineering characteristics). Additionally, a component planning matrix was created, resulting in three key components for the tool's development: the main frame, slicing mechanism, and slicing blade. The next step involved designing and constructing the cassava slicing tool based on user requirements. The developed cassava slicing device was constructed from iron and was equipped with three blades mounted on a rotating disc, which was operated manually using a hand crank. The device also features a container for placing the cassava, fitted with a spring mechanism that facilitates the movement of the cassava toward the blades. The testing results of the developed tool showed a 6.1% improvement in slicing time efficiency and a 0.54% increase in slicing yield. Moreover, the tool development helped minimize the risk of hand injuries from the blade and eliminated waste during the cassava slicing process. Bahasa Indonesia Abstract: Penelitian ini dilakukan dengan tujuan untuk merancang dan mengembangkan alat pengiris singkong pada UMKM Keripik Singkong Bu Supiah yang terletak di Desa Keranggan. Proses perancangan dan pengembangan alat ini dilakukan dengan pendekatan Quality Function Deployment (QFD) yang digunakan untuk mengumpulkan kebutuhan pengguna (voice of customers) yang kemudian akan dianalisis lebih lanjut untuk menghasilkan HOWs (engineering characteristics). Selain itu, terdapat matriks perencanaan komponen yang menghasilkan tiga komponen penting dalam pengembangan alat, yaitu kerangka utama, mekanisme pengirisan, dan pisau pengiris. Proses selanjutnya adalah perancangan dan pembuatan alat pengiris singkong berdasarkan kebutuhan pengguna. Alat pengiris singkong yang dikembangkan terbuat dari besi dengan 3 bilah pisau dipasang pada piringan dan dioperasikan menggunakan engkol yang diputar secara manual. Pada alat tersebut juga terdapat wadah tempat meletakkan singkong yang dilengkapi dengan pegas yang dapat mendorong singkong ke arah pisau. Hasil uji coba dari alat yang telah dikembangkan adalah terdapat peningkatan efisiensi sebesar 6,1% terhadap waktu pengirisan singkong dan peningkatan sebesar 0,54% terhadap hasil irisan singkong. Selain itu, pengembangan alat juga dapat meminimalkan resiko tangan tergores mata pisau dan menghilangkan waste yang terdapat dalam proses pengirisan singkong.